Maximal 3-local subgroups of symmetric groups - Punnzeyar Patthanangkoor (2018)
The subgroups in the set Ν max (G,B) consisting of all maximal 3-local subgroups of G = Sym(n) with respect to B, the normalizer of a Sylow 3-subgroup of G in G, is investigated. Additionally, the structure of the subgroups in Ν max (G,B) was determined.